PERAN PENGELOLAAN WAKAF UANG DALAM MENINGKATKAN KESEJAHTERAAN UMAT - Prakasa, Novan Adi; Indrarini, Rachma (Universitas Negeri Surabaya, 2023)
Waqf is not just worship but if waqf is run properly, waqf has an important role such as improving the welfare of the people. The purpose of this research is to see the role of cash waqf management in improving the welfare of the people. The method used is qualitative with literature study analysis. The results obtained are that cash waqf has a role in improving the welfare of the people. Along with technological developments, cash waqf is managed and distributed in many ways. However. There are still waqifs who are still carrying out cash waqf activities through local institutions or foundations. The majority of the use of cash waqf is collected and managed to become productive waqf. There are productive waqf that are developed with entrepreneurship, training, vacant land management, education, agriculture, and plantations. The benefits and results of productive waqf are what can prosper the people and the results obtained can be distributed to other less fortunate communities.